Calibration methods of industrial robots - Pytel, Ivan; Vasylyk, Maksym; Makal, Jaroslaw (Видавництво Львівської політехніки, 2024)
Robotization is one of the crucial directions of modernizing today's industrial production. Robotic systems offer solutions to many different challenges. However, their implementation is constrained by limited accuracy, which is inferior to conventional machine tools. A way to improve industrial robots' accuracy is to calibrate them, i.e., eliminate factors that affect accuracy by refining the mathematical models for software correction of manufacturing and assembly errors, as well as elastic and thermal deformations.
Keywords: robotics; accuracy; calibration; metrology; modeling